Optimizing Information Systems in the Food Supply Chain: Strategies for Sustainable Food Security in Lampung Province - Maulana Agung; Jeni Wulandari; May Roni (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to analyze and develop strategies for optimizing information systems in the food supply chain in order to strengthen sustainable food security in Lampung Province. Inefficient food supply chains and the lack of information system integration at the producer, distributor, and consumer levels are major challenges in ensuring the stability of local food supply and distribution. Using a qualitative approach through case study methods, this research was conducted through in-depth interviews, field observations, and Focus Group Discussions (FGD) with key players in the regional food system. Data analysis was conducted using the SWOT and system analysis approaches, then strategies based on the Logical Framework Approach (LFA) and Technology Acceptance Model (TAM) were formulated as a reference in developing an adaptive and contextual information system. The results of the study show that optimizing information systems can increase supply chain transparency, accelerate information flow, and reduce potential crop losses. This study provides strategic contributions to regional policy makers, as well as serving as a reference for the development of digital-based food information systems in other regions with similar characteristics. The results of this study will be published in a reputable Scopus journal or international seminar, with a technology readiness level (TRL) index of 3–5 and the potential to be registered as intellectual property rights.